2002
DOI: 10.1007/s00427-001-0208-x
|View full text |Cite
|
Sign up to set email alerts
|

mPet-1, a mouse ETS-domain transcription factor, is expressed in central serotonergic neurons

Abstract: Here we describe the expression pattern of a previously unknown mouse gene mPet-1. The isolated cDNA codes for an ETS-domain transcription factor of 237 amino acids in length, which is localized to the nucleus. mPet-1 is a member of the winged helix transcription factor gene family like its rat homologue Pet-1 and the human homologue FEV. The start ATG of mPet-1 and the size of the predicted protein are identical to the human FEV. The mPet-1 protein is clearly smaller since it lacks the first 103 N-terminal am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 7 publications
4
47
0
Order By: Relevance
“…The Ets family contains some 30 different members, of which Erg and Fli-1 are most closely related to Pet-1. In the present study, we have identified one zebrafish homologue of Pet-1 showing 89% identity to mouse Pet-1 within the Ets domain (Pfaar et al, 2002). As reported for mammals (Peter et al, 1997;Fyodorov et al, 1998;Pfaar et al, 2002), the main form of zebrafish Pet1 is encoded by three exons.…”
Section: Organization Of the Zebrafish Pet1 Genesupporting
confidence: 70%
See 3 more Smart Citations
“…The Ets family contains some 30 different members, of which Erg and Fli-1 are most closely related to Pet-1. In the present study, we have identified one zebrafish homologue of Pet-1 showing 89% identity to mouse Pet-1 within the Ets domain (Pfaar et al, 2002). As reported for mammals (Peter et al, 1997;Fyodorov et al, 1998;Pfaar et al, 2002), the main form of zebrafish Pet1 is encoded by three exons.…”
Section: Organization Of the Zebrafish Pet1 Genesupporting
confidence: 70%
“…In the present study, we have identified one zebrafish homologue of Pet-1 showing 89% identity to mouse Pet-1 within the Ets domain (Pfaar et al, 2002). As reported for mammals (Peter et al, 1997;Fyodorov et al, 1998;Pfaar et al, 2002), the main form of zebrafish Pet1 is encoded by three exons. However, we identified for this transcript 39 additional base pairs in the fish genome, giving rise to 13 additional N-terminal aa, which we could not find in other species by in silico search.…”
Section: Organization Of the Zebrafish Pet1 Genesupporting
confidence: 70%
See 2 more Smart Citations
“…The onset of Pet-1 expression in the mouse brain occurs at approximately embryonic day 11 (E11) in postmitotic precursors within the mantle layer (Pfaar et al, 2002;Pattyn et al, 2003). Expression is restricted to two bilateral longitudinal hindbrain domains at the level of rhombomeres r1-r3 and r5-r8.…”
Section: Z Expression Recapitulates the Temporal Expression Pattermentioning
confidence: 99%